The Implementation of Contantia Justitia in Religious Courts During the COVID-19 Pandemic - Putra, Muhammad Yusuf; Puluhulawa, Fenty U.; Kasim, Nur Mohamad (Universitas Negeri Gorontalo, 2023)
This study aims to examine the Implementation of E-Court during the COVID-19 Pandemic as a Support for the Contante Justitie Principle in the Religious Courts. This type of research is empirical legal research, which uses a qualitative approach method, with Primary Data sources obtained directly. The results showed that the implementation of the Electronic Justice System (E-Court) during the Covid-19 Pandemic at the Gorontalo Class 1A Religious Court was comprehensively in accordance with the principles of Contantia Justitia or simple, fast and low cost justice, because it had been implemented from the time of receipt and registration of cases to the reading of case decisions carried out electronically using online applications that had been officially developed by the Supreme Court such as e-Filling (case registration), e-Payment (case fee), e-Summons (Summons of Parties), e-Litigation (trial), e-Copy (Copy of Decision), and e-Sign (Signature), and supported by online communication channel applications such as zoom cloud meeting, google meet, email, and even telephone lines.